Exploring ambiguous realms: Access, exposure and agency in the interactions of rural Zambian children. (August 2016) - Clemensen, Nana
In Hang'ombe Village in southern Zambia, the relative lack of physical boundaries between the activities of family members allow children to observe the actions and discussions of adults on close hand, exposing them to the ambiguities of daily life. Children explore these ambiguities in their interactions, testing social roles and conventions. This article explores the vigilance and creative agency displayed by Hang'ombe children, in an environment spurring their acquisition of distinct social and linguistic skills.